From Anti-allergic to Anti-Alzheimer’s: Molecular Pharmacology of Dimebon™ - Okun, I.; Tkachenko, S. E.; Khvat, A.; Mitkin, O.; Kazey, V.; Ivachtchenko, A. V. (Current Alzheimer Research, 2010)
Dimebon, originally developed as an anti-histamine drug, is being re-purposed for new indications as an effective treatment for patients suffering from Alzheimer's and Huntington’s diseases, albeit with an as-yet unknown mechanism of action. We have performed molecular pharmacology profiling of this drug on a panel of 70 targets to characterize the spectrum of its activity, with the goal to possibly elucidate a potential molecular mechanism for the re-purposing of this drug candidate. We show that in addition to histaminergic receptors, Dimebon exhibits high affinity to a constellation of other receptors; specifically serotonergic, alpha-adrenergic and dopaminergic receptors. Good correlations with published literature were obtained for the affinity of Dimebon to inhibit butyrylcholinesterase, interact with H1and H2 receptors (Ki = 2 nM and 232 nM), and to block histamine-induced calcium fluxes in cells. Within serotonergic receptor subtypes, Dimebon shows highest affinity for 5-HT7 (Ki=8 nM) and 5-HT6 (Ki=34 nM) receptors, with the relative affinity rank-order of 5-HT7 > 5-HT6 ≥ 5-HT2A = 5-HT2C > 5-HT1A = 5-HT1B > 5-HT2B=5-HT3. Dimebon also interacts with adrenergic receptor subtypes (rank-order: α1A (Ki = 55 nM)= ≥1B ≥ α2A (Ki = 120 nM) = α1D), and dopaminergic receptor subtypes (rank-order: D1=D2S=D2L (Ki ∼ 600 nM) >D3≥D4.2>D4.4≥D4.7). These results demonstrate a molecular pharmacological basis for re-purposing of this drug to new therapeutic areas. The informed targeting of the combined molecular target activities may provide additional advantages for patients suffering from similar diseases syndromes. Understanding the role that different pathways play in diseases with complex etiologies may allow for the rational design of multi-target drugs.
Keywords: Alzheimer' s disease